Addition of Nitrogen Increases Variability of Vegetation Cover in an Arid System with Unpredictable Rainfall - Seymour, Colleen L.; Milton, Suzanne J.; Altwegg, Res; Joseph, Grant S.; Dean, W. Richard J. (Ecosystems (New York), 2020)
Addition of nitrogen (N) to rangeland that has been degraded through overgrazing or drought can hasten vegetation recovery. Additional N may influence temporal stability of vegetation cover, however, and change species composition. Potassium (K), by contrast, may help plants survive dry periods, increasing stability. Plant longevity also influences cover stability, but few studies have investigated effects of additional N or K on relative representation of species’ longevities within plant communities. In a semi-arid shrubland, we manipulated N and K in a 2 × 2 factorial experiment (treatments were addition of N, K, K and N, or control) in 12 plots, monitoring vegetation cover and plant species composition over 20 years (1998–2018). We assessed above-ground cover, stability of cover, and changes in community composition. Although responses to additional nutrients might be expected to be muted in this arid system where water is limiting, treatments differed significantly in cover, temporal stability, and species composition. N was associated with greater cover, but with lower stability of cover. Once nutrient addition and lifespan had been accounted for, stability was higher for transects with greater species richness at the start of the experiment. Short-lived species increased and long-lived species decreased in N plots. Additional K increased stability of short-lived species’ cover and moderated changes in species composition associated with additional N. Although N can increase cover, it is also associated with greater variability, which is particularly relevant given expected increases in rainfall variability with climate change. The moderating effect of K suggests that it may assist in restoration of areas that have experienced high N addition owing to past management practices.